PERENCANAAN PENINGKATAN KUALITAS PRODUK KOMPOR DI SENTRA INDUSTRI KECIL KOMPOR MALANG DENGAN METODA PENGENDALIAN KUALITAS STATISTIK (STUDI KASUS DI SENTRA INDUSTRI KOMPOR MERJOSARI MALANG) - Mohammad Lukman, Mohammad Lukman (Jurnal Gamma, 2006)
Stove Industry in Malang town have the central which is located in Merjosari village of LowokwaruDistrict, competition sharply felt in stove segment of middle to below level, so that many small industry iswhich big before and now withdraw even some of closing down because unable to compete in market at thismoment domestic stove product competition is more strict, proven by the big factory like PT. Maspion PTKuwatsu and others and also small factory under it more much its amount. Theoretically basic competition isthe quality of product in this matter is stove product; have to be suitable with expectation of customer asaccording to market segmentation which is made by small entrepreneur. Improving of competition accordingto M. Porter one of them is by improving the quality of product, in this case is stove product by doingdevelopment of some control concept of quality during process of making from raw material of stove untilpackaging of stove product without change the design or total job system of stove production process. Toget the stove product which with quality, hence during stove production process must be done a planningof quality, one of them is by the quality control method of statistically (PKS or, Statistical Process Control,SPC).Based on observation that found, there are some problem faced by small company or industry ofstove there is no system of planning of production control which correct. Along of that?s trying to doresearch of the stove small industrial to be able to plan the control of quality for the control of stove product.Result of this first phase research is a profile picture of stove quality in stove small industrial central ofMerjosari village.Conclusion from this research is the first effect of defect stove product of the most have a lot offrequency is at the tank production process, the reason is existence of trace material that have got theproduction process before. Both calculation process of the quality control based on attribute effect of defectis in control in quality. Third profile of control quality is like in diagram picture of statistical control, its meanthat all process of making stove tank still in limit of quality control of its attribute.